Musical Ear Syndrome and Cochlear Explantation: Case Report and Proposal for a Theoretical Framework. Issue 10 (December 2019) - Kompis, Martin; Mantokoudis, Georgios; von Gunten, Benjamin; Schmid, Christoph; Blaser, Daniela; Caversaccio, Marco
Abstract : Objective: To report an unusual case of musical ear syndrome, and to present a theoretical framework for this condition, merging information from the presented case and from former case reports. Patient: A 67-year-old semi-professional musician, who underwent bilateral cochlear implantation and experienced musical ear syndrome, i.e., hearing music, where none was present. Interventions: Cochlear implantation with a bilateral cochlear implant, and cochlear explantation 17 months later. Main Outcome Measure: Report of presence or absence of musical ear syndrome by the patient. Results: Musical ear syndrome started 1 day after implantation. It ceased immediately after cochlear explantation, but reappeared 3 months later. Conclusions: Several types of factors seem to determine whether a musical ear syndrome is present or not. We propose to differentiate between triggers, modifiers, and conditions, which determine a base vulnerability. Vulnerability seems to be increased by auditory deprivation and by habitual retrieval of music from memory. Cochlear implantation or explantation seems to act as triggers. The proposed framework may help to stimulate reporting of more potentially relevant factors in future case reports on musical ear syndrome, and ultimately to help to understand this condition better.